DINAMIKA PEMIKIRAN NAHDLATUL ULAMA DALAM MERESPONS KEPEMIMPINAN NON MUSLIM DI INDONESIA - Izzul Madid (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
The leadership of non-Muslims in Indonesia had become a hot spotlight when the action 212 was held. Many people who later conducted a study of Islamic law about the validity of a non-Muslim was appointed as a leader. One study of this matter that is quite unique is the result of the Bahtsul Masail held by the GP Ansor which resulted in a conclusion that a non-Muslim is legitimately appointed as a leader in Indonesia. The results of this study reaped polemics because by some circles, it was considered to harm NU's thoughts which had been decided at the 1999 Congress at Lirboyo. This article intends to explore how NU's real thinking as a Muslim mass organization is the largest in responding to non-Muslim leadership in the Indonesian context. From the results of this study, it was concluded that organizationally, NU had never discussed the issue of non-Muslim leadership specifically, either in the Congress or National Conference of Alim Ulama. The issue that has been raised by NU in relation to non-Muslim politics is around its electability as a legislative council.